Spine Injuries Sustained After Falls While Crossing the U.S.-Mexico Border - Hannah R. Riva; Michael M. Polmear; Cyrena Petersen; June Y. Guillet; Taylor M. Yong; Adam H. Adler; Rajiv Rajani; Vishwajeet Singh; David Chin Sing Wang (Neurotrauma Reports)
This study is to report the demographics, incidence, and patterns of spinal injuries associated with border crossings resulting from a fall from a significant height. A retrospective cohort study was performed at a Level I trauma center from January 2016 to December 2021 to identify all patients who fell from a significant height while traversing the U.S.-Mexico border and were subsequently admitted. A total of 448 patients were identified. Of the 448 patients, 117 (26.2%) had spine injuries and 39 (33.3%) underwent operative fixation. Females had a significantly higher incidence of spine injuries (60% vs. 40%; p < 0.00330). Patients with a spine fracture fell from a higher median fall height (6.1 vs. 4.6 m; p < 0.001), which resulted in longer median length of stay (LOS; 12 vs. 7 days; p < 0.001), greater median Injury Severity Score (ISS; 20 vs. 9; p < 0.001), and greater relative risk (RR) of ISS >15 (RR = 3.2; p < 0.001). Patients with operative spine injuries had significantly longer median intensive care unit (ICU) LOS than patients with non-operative spine injuries (4 vs. 2 days; p < 0.001). Patients with spinal cord injuries and ISS >15 sustained falls from a higher distance (median 6.1 vs. 5.5 m) and had a longer length of ICU stay (median 3 vs. 0 days). All patients with operative spine injuries had an ISS >15 relative to 50% of patients with non-operative spine injuries (median ISS 20 vs. 15; p < 0.001). Patients with spine trauma requiring surgery had a higher incidence of head (RR = 3.5; p 0.0353) and chest injuries (RR = 6.0; p = 0.0238), but a lower incidence of lower extremity injuries (RR = 0.5; p < 0.001). Thoracolumbar injuries occurred in 68.4% of all patients with spine injuries. Patients with operative spine injuries had a higher incidence of burst fracture (RR = 15.5; p < 0.001) and flexion-distraction injury (RR = 25.7; p = 0.0257). All patients with non-operative spine injuries had American Spinal Injury Association (ASIA) D or E presentations, and patients with operative spine injuries had a higher incidence of spinal cord injury: ASIA D or lower at time of presentation (RR = 6.3; p < 0.001). Falls from walls in border crossings result in significant injuries to the head, spine, long bones, and body, resulting in polytrauma casualties. Falls from higher height were associated with a higher frequency and severity of spinal injuries, greater ISS, and longer ICU length of stay. Operative spine injuries, compared with non-operative spine injuries, had longer ICU length of stay, greater ISS, and different fracture morphology. Spine surgeons and neurocritical care teams should be prepared to care for injuries associated with falls from height in this unique population.